Networks in the Modern Economy: Mexican Migrants in the U. S. Labor Market - Munshi, K. (Quarterly Journal of Economics, 2003)
This paper attempts to identify job networks among Mexican migrants in the U. S. labor market. The empirical analysis uses data on migration patterns and labor market outcomes, based on a sample of individuals belonging to multiple origin-communities in Mexico, over a long period of time. Each community’s network is measured by the proportion of the sampled individuals who are located at the destination (the United States) in any year. We verify that the same individual is more likely to be employed and to hold a higher paying nonagricultural job when his network is exogenously larger, by including individual xed effects in the employment and occupation regressions and by using rainfall in the origin-community as an instrument for the size of the network at the destination. I.